Chemical and functional properties of cassava starch, durum wheat semolina flour, and their blends - Oladunmoye, O.; Aworh, O.; Maziya-Dixon, B.B.; Erukainure, O.; Elemo, G.N. (Wiley, 2014)
High-quality cassava starch (HQCS) produced from high-yielding low-cyanide improved cassava variety, TMS 30572, was mixed with durum wheat semolina (DWS) on a replacement basis to produce flour samples containing 0, 20, 30, 50, 70, and 100% cassava starch. They were analyzed for chemical composition (proximate, amylose, free sugars, starch, wet gluten, and cyanide) and functional properties (pasting, swelling power, solubility, water absorption, water binding, starch damage, diastatic and ?-amylase activity, dough mixing, and stability). Protein, carbohydrate, fat, and ash of flour samples ranged from 0.75–12.31%, 70.87–87.80%, 0.95–4.41%, and 0.12–0.83%, respectively. Cyanide levels in all the flour samples were less than 0.1 ppm. Amylose content varied between 19.49% for cassava and 28.19% for wheat, correlating significantly with protein (r = 0.95, P = 0.004) and ash contents (r = 0.92, P = 0.01) at 5%. DWS and HQCS had similar pasting temperatures (50.2–53°C), while other pasting properties increased with increasing levels of HQCS. Dough mixing stability of samples decreased with increasing levels of HQCS. All the flour samples had ?-amylase activity greater than 200. Both HQCS and DWS compare favorably well in swelling power (7.80–9.01%); but the solubility of wheat starch doubled that of cassava. Starch damage varied between 3.3 and 7.2 AACC for semolina and starch, with the latter having higher absorption rate (97%), and the former, higher absorption speed (67 sec). Results obtained showed positive insight into cassava–wheat blend characteristics. Data thus generated provide additional opportunities of exploiting cassava utilization and hence boost its value–addition potentials for product development.